Avaliação in vitro da interação entre aspirina e a metformina no câncer de mama : participação das lipoxinas e da COX-2 - Amaral, Maria Eduarda Azambuja (2018)
Background Breast cancer is highly prevalent among women worldwide. It is classified into three main subtypes: the estrogen receptor positive (ER+), the human epidermal growth factor receptor 2 positive (HER2+), and the triple negative breast cancer (TNBC). This latter type is the most prevalent in clinics. Each type requires a specific treatment, being TNBC an actual challenge for treating. Drug repurposing is an easy and cheaper methodology to identify new therapies for cancer treatment. This study evaluated the effects of aspirin and metformin, isolated or in combination, in breast cancer cells of different subtypes. Methods The breast cancer cell lines MCF-7, MDAMB- 231, and SK-BR-3 were treated with aspirin and/or metformin (0.01 mM - 10 mM); functional in vitro assays were performed. The interactions with the estrogen receptors (ER) were evaluated in silico. Results Metformin altered the morphology, and reduced the viability and migration of the ER+ cell line MCF-7. A synergistic effect for the combination of metformin and aspirin was observed in the TNBC cell subtype MDAMB- 231, according to the evaluation of viability and colony formation. No significant effects were observed for either drugs in the HER2+ cell subtype SK-BR-3. The effects of metformin and aspirin partly rely on cyclooxigenase-2 (COX-2) upregulation, without any alteration of lipoxin production. In silico, metformin and aspirin bound the ERa receptor with the same energy. Conclusion We provide novel evidence on the mechanisms of action of aspirin and metformin in breast cancer cells, showing favorable outcomes for these drugs in the ER+ and TNBC subtypes.